Centralized use of decentralized technology: Tokenization of currencies and assets - Ying Zhang; Bing Gong; Peng Zhou (Cardiff University, Cardiff Business School, 2024)
This paper presents a thorough examination of centralized use of a decentralized technology (blockchain) in monetary and financial systems at the national level. A comparative study is conducted to summarize the regulatory and legislative frameworks of currency/asset tokenization in seven major economies (US, EU, UK, Switzerland, Australia, Japan, and South Korea). China is then used as a case study to explore how blockchain technology is adopted to enable central bank digital currency, bond tokenization, and "currency bridge". Based on various contexts analyzed, we extend the Technology Acceptance Model, highlighting the roles of perceived benefits, perceived risks, and collaborative leadership in building trust in and promoting adoption of tokenization. Policymakers and practitioners are recommended to follow a gradual, eclectic, and collaborative approach to tokenization.
Keywords: 330; Blockchain; Tokenization; CBDC; Decentralization; Collaborative Leadership